Acute Ischemic Stroke Infarct Topology: Association with Lesion Volume and Severity of Symptoms at Admission and Discharge - Payabvash, S.; Taleb, S.; Benson, J.C.; McKinney, A.M. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Acute stroke presentation and outcome depend on both ischemic infarct volume and location. We aimed to determine the association between acute ischemic infarct topology and lesion volume and stroke severity at presentation and discharge.MATERIALS AND METHODS: Patients with acute ischemic stroke who underwent MR imaging within 24 hours of symptom onset or last seen well were included. Infarcts were segmented and coregistered on the Montreal Neurological Institute-152 brain map. Voxel-based analyses were performed to determine the distribution of infarct lesions associated with larger volumes, higher NIHSS scores at admission and discharge, and greater NIHSS/volume ratios.RESULTS: A total of 238 patients were included. Ischemic infarcts involving the bilateral lentiform nuclei, insular ribbons, middle corona radiata, and right precentral gyrus were associated with larger infarct volumes (average, 76.7 ± 125.6 mL versus 16.4 ± 24.0 mL, P < .001) and higher admission NIHSS scores. Meanwhile, brain stem and thalami infarctions were associated with higher admission NIHSS/volume ratios. The discharge NIHSS scores were available in 218 patients, in whom voxel-based analysis demonstrated that ischemic infarcts of the bilateral posterior insular ribbons, middle corona radiata, and right precentral gyrus were associated with more severe symptoms at discharge, whereas ischemic lesions of the brain stem, bilateral thalami, and, to a lesser extent, the middle corona radiata were associated with higher ratios of discharge NIHSS score/infarct volume.CONCLUSIONS: Acute ischemic infarcts of the insulae, lentiform nuclei, and middle corona radiata tend to have larger volumes, more severe presentations, and worse outcomes, whereas brain stem and thalamic infarcts have greater symptom severity relative to smaller lesion volumes.VLSMvoxel-based lesion symptom mapping